A STUDY OF VARIETIES OF WRITTEN ENGLISH IN NIGERIA (1973)
The study postulates three varieties of English performance in the writings of Nigerians, and examines these in detail for their "common core" features and their "indexical markers". In the Introduction is discussed the English in present-day Nigeria with a theoretical cline of the varieties erected, the pivot around which the investigations of the later chapters are hung. The second chapter examines specifically varieties three and two in the performance of Nigerian judges, while the third deals with the use of English in the Nigerian newspaper press. Chapter IV examines first-variety usage in Literary Nigerian English and the fifth chapter undertakes an examination of the language ability of the low grade workers of the University of Ibadan, exponents of the first variety. Chapter VI, the final chapter, summarizes the findings of the investigations, makes some concluding statements, and suggests four possibilities for further research into Nigerian English. In essence, the study identifies the linguistic features common to all the varieties examined, and their indexical markers. The study also suggests that, from the evidence of the thesis, third-variety performances in written English in Nigeria be regarded as Standard (Educated) written Nigerian English.